Urban Gardening System for Home Organic Vegetables: LED Artificial Light and Irrigation Control - Napat Watjanatepin (Journal of Engineering and Technological Sciences, 2020)
Due to the limited amount of space in urban homes, the trend of indoor gardening is growing as it is the most suitable gardening method in the specified environment; moreover, it provides the possibility of growing organic vegetables at home. This paper presents the design and construction of an urban indoor gardening system for growing organic vegetables, with automated functions. LEDs in the spectra of R (637 nm) B (455 nm) and white (3500 K) were applied as horticultural light and were designed using the horticulture lighting calculation tool. The automated irrigation system was controlled by Arduino-based soil moisture sensors. The urban indoor gardener prototype had a cultivation bed of 0.385 m2. The results showed that the LED panel could emit a photosynthetic photon flux density of around 200 ± 7 µmol m-2s-1 with an R to B ratio of 0.7 ± 0.04, and a photoperiod of 16 h per day. The soil moisture control system is automatic and can regulate the soil moisture to the appropriate percentage for agricultural use, which is 50% to 69%. Consequently, it is able to save water and provide an alternative method for efficient water use. The urban indoor gardening system is compact and can be placed in a small indoor corner. The presented system was able to produce organic green-oak lettuce with a weight of 1272.54 g/crop in a restricted area, providing an ease-of-use experience and requiring very little maintenance.